Development of the University of Massachusetts Medical School Library - Brown, Cynthia Roblin (1969)
The creation of a library for the new Medical School of the University of Massachusetts presents an interesting opportunity to see how the principles of administrative technique, which have been found so effective in other areas of business and management, can be applied to the library profession. The solution of the logistical problem of having a base in Amherst and a field in Worcester lends itself to the prescribed pattern of progression from consultation to decision, decision to policy, and policy to action. The same pattern also emerges in the relationship of the librarian to the architect.